Total weight loss rather than preoperative body mass index correlates with remission of irregular menstruation after sleeve gastrectomy in patients with polycystic ovary syndrome - Zhao, Yian; Xiong, Sisi; Liu, Teng; Shu, Jiaxin; Zhu, Tao; Li, Shumin; Zhong, Mingwei; Zhao, Shigang; Huang, Xin; Liu, Shaozhuang (Frontiers in Endocrinology, 2024)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy affecting reproductive-aged women. Some retrospective studies with small sample sizes have reported that bariatric metabolic surgery is effective in remission of irregular menstruation in patients with PCOS and obesity. However, the correlation between preoperative body mass index (BMI), postoperative weight loss, and remission of irregular menstruation in patients with obesity and PCOS after sleeve gastrectomy (SG) is lack of consensus. We enrolled 229 participants with obesity and PCOS who underwent SG. All patients were followed up for one year after surgery. Remission of irregular menstruation was defined as a spontaneous consecutive six-month menstrual cycle in one year.Subgroup analysis was conducted using tertiles of preoperative BMI and postoperative total weight loss (TWL)% to determine their correlation with the remission of irregular menstruation after SG. 79.03% (181/229) patients achieved remission of irregular menstruation one year after SG with a TWL% of 33.25 ± 0.46%. No significant difference was detected in the remission rate among the subgroups with different BMI (P=0.908). TWL% was correlated with the remission of irregular menstruation (OR 1.78, 95% CI 1.18-2.69, P<0.05). SG had a significant effect on the remission of irregular menstruation in patients with obesity and PCOS. Preoperative BMI did not emerge as a decisive factor correlated with remission; instead, TWL% showed potential as a key factor.